Effectiveness of the policy on converting structural positions to functional positions at the Regional Development Planning Agency (Bappeda) Of Padang City - Najmy, Rain; Malau, Hasbullah (Privietlab, 2025)
Bureaucratic reform in Indonesia concerning the simplification of structures by transforming positions from structural to functional positions has been issued, starting with SE MenPANRB No. 391/2019 and implemented through PermenPANRB No. 17/2021. However, at the regional level, regulatory synchronization and operational readiness are often imbalanced. This is because the sequence of issuance of laws, regulations, and instructions (for example, the equalization mechanism precedes structural simplification) and the unavailability of adequate technical guidelines cause implementation gaps in the project. The Padang City Bappeda is a relevant case study. The need for 47 new functional positions should be filled, yet only 17 have been fulfilled; even promotions, transfers, and deaths of employees are not balanced with quick filling mechanisms and post-equalization training/certification availability. This study analyzes the effectiveness of the policy using a qualitative descriptive approach through a purposive sample of key officials and civil servants. Data were collected through in-depth interviews and documentation, validated using source triangulation, and analyzed using reduction, presentation, and conclusion drawing. The results showed insufficient formation of functional officers, a mismatch of competency with position, an administrative system that was not efficient and integrated, and the absence of a job map based on workload analysis. Viewed through the lenses of Dunn's framework, dimensions such as effectiveness, efficiency, adequacy, responsiveness, and precision have not been optimally achieved in the current study. As a result, the workload was concentrated on a few functional officers, often handling multiple subfields; this, in turn, slowed data/planning services and reduced the quality of strategic decision-making. Therefore, in the face of a shortage of functional officers in Bappeda Kota Padang, it is recommended that the regional government immediately prepare and implement clear and integrated technical regulations on the functional position staffing mechanism.